?Age and Sex Dependence of Copper, Nickel, Lead and Zinc Levels in Scalp Hair of Urban Pakistani Population: ?Short Communication (Biological Sciences - PJSIR, 1995)
diluted with 5% nitric acid [7] to 25.00 ml and was aspirated for the determ ination of the selected metals. A Hitach iatom ic absorption spectrophotometer. model 170-\ 0 was used throughout this work, Spectroscopic grade chemicals (purity >99.9%) were used for the preparation of standards.